Effects of Lengthening Velocity During Eccentric Training on Vastus Lateralis Muscle Hypertrophy - Marzilger, Robert; Bohm, Sebastian; Mersmann, Falk; Arampatzis, Adamantios (Frontiers in Physiology, 2019)
Eccentric loading is an effective stimulus for muscle hypertrophy and strength gains, however, the effect of lengthening velocity is under debate. The purpose of the current study was to investigate the influence of muscle lengthening velocity during eccentric training on muscle hypertrophy and strength gains at a given overall loading volume. Forty-seven participants were randomly assigned to a control (n=14, age: 26.9±4.1 y) and an experimental group (n=33, age: 27.1±4.4 y). Each leg of the participants in the experimental group was randomly assigned to one of four eccentric training protocols with different angular velocities (i.e. 45°/s, 120°/s, 210°/s and 300°/s). Both the magnitude of loading (100% of the isometric maximum) and overall time under tension was matched between the protocols. The training was performed for 33 session, three times per week with 5 training sets per session. Before and after the intervention the maximum isometric knee extension moments were measured in all groups using dynamometry, vastus lateralis (VL) muscle anatomical cross–sectional area and VL muscle volume were measured in the experimental group using magnetic resonance imaging. Data was analyzed in a mixed-design analysis of variance. After the training intervention the maximum knee joint moments increased in the experimental group (14.2%, p<0.05) but not control group. VL anatomical cross-sectional area and VL muscle volume increased significantly (p<0.05) in the experimental group (5.1% and 5.7%, respectively), but we did not find any significant differences between the four training protocols in all investigated parameters (p>0.05). The present study provides evidence that muscle hypertrophy and strength gains after eccentric exercise is velocity-independent when load magnitude and overall time under tension are matched between conditions. This is likely due to the similar mechanical demand for the muscle induced by the loading conditions of all 4 training protocols. The better control of motion and the potentially decreased joint loading compared to high lengthening velocity contractions support the application of slow eccentric exercises in special populations like elderly and people with neurological and musculoskeletal diseases.